Edward Taylor - American Writers 52 : University of Minnesota Pamphlets on American Writers - Stanford, Donald E. (Donald Elwin), 1913-1998 (Book collections on Project MUSE., 1965)
Edward Taylor - American Writers 52 was first published in 1965. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.